Pertumbuhan dan Sporulasi Trichoderma sp. Pada media jagung dan dedak di Laboratorium Pengamatan Hama Penyakit Tanaman Pangan dan Hortikultura (PHPTPH) Lebaksari Pandaan Pasuruan - Supyanto; Argus (Program Studi Biologi Fakultas Matematika dan IPA Universitas Annuqayah, 2025)
Trichoderma is one of the biological control agents that has been proven effective in controlling plant pests (OPT). Trichoderma can suppress the development of pathogenic fungi in durian plants by 99%. Making Trichoderma sp. growth media on a large scale requires a lot of money, therefore alternative materials are needed to replace rice as the main ingredient in making mushroom growth media. Therefore, corn and bran media are used because the nutritional content of both media is sufficient for the growth of Trichoderma sp. fungi. This study aims to compare the effectiveness of corn and bran media on the growth of Trichoderma sp. The experiment was conducted at the PHPTPH Pandaan Laboratory, Pasuruan for one month. The results showed that corn media accelerated mycelium growth, while bran media produced higher spore density.